Knowledge and Attitude of Medical Students about Insulin Resistance Symptoms, Effect, and Treatment - Shihab, Alaa Saber (Journal for Research in Applied Sciences and Biotechnology, 2023)
The inability of the target organs to react appropriately to the action of insulin is known as insulin resistance. Insulin resistance impairs insulin-mediated glucose absorption in the peripheral (skeletal muscle and adipose tissue), which results in increased blood sugar levels and increase insulin demand. Aim: This study aims to assess medical students' knowledge and attitudes on the signs, consequences, and treatments of insulin resistance. Patients and methods: There were 160 medical students at Tikrit University in all, male and female. The average age of students in the primary stages was 20 years, while that of students in the clinical stages was 23 years old. The current study, which was conducted in 2023 at Tikrit University College of Medicine (TUCOM), is cross-sectional in nature. All data presented statically as percentage. Results: There are three forms of diabetes mellitus, according to 43.75 percent of medical students. One of the complications of DM, according to (90.63 %) of them, is vision problems. Diet modification and exercise were preferable than oral hypoglycemic drugs and insulin therapy. Conclusions: The study found that (75%) of medical students recognized the link between type 2 DM and insulin resistance, with clinical students showed a higher level of awareness in comparison with preclinical students.